1998
DOI: 10.1007/bf02457402
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of research productivity

Abstract: Earlier researchers like Turkeli, suggested that 'the factors which determine the productivity of scientists are admittedly complex and perhaps not amenable to real scientific analysis'. The present investigation was designed with the sole purpose of confronting such a complex problem. Nearly 200 variables influencing research productivity were collected through relevant literature, analysis of biographies of great scientists, and discussion with eminent scientists. Finally, through a critical examination, 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Previous studies have suggested that publication rate also depends on a wide range of factors that cannot easily be measured, such as: the availability of research funds; teaching loads; equipment; research assistants; workload policies; departmental culture and working conditions; organisational context; and talent and hard work (see e.g. Dundar & Lewis, 1998;Kyvik, 1993;Ramesh & Singh, 1998). Moreover, the process of cumulative advantage (Merton, 1968) implies that minor differences early in a career may result in substantial differences in achievement by the end of a career.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that publication rate also depends on a wide range of factors that cannot easily be measured, such as: the availability of research funds; teaching loads; equipment; research assistants; workload policies; departmental culture and working conditions; organisational context; and talent and hard work (see e.g. Dundar & Lewis, 1998;Kyvik, 1993;Ramesh & Singh, 1998). Moreover, the process of cumulative advantage (Merton, 1968) implies that minor differences early in a career may result in substantial differences in achievement by the end of a career.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation can be supported by the fact that they also tend to more frequently be authors of review papers and that the authors of review papers tend to have more references in their regular publications. Along this line, Ramesh Babu and Singh () indicated that it is almost impossible to be a productive scientist without awareness of what others are doing in your area of specialization and that an acquaintance with recent trends of research in the context of a global situation is inevitable for raising one's own research output.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions have important implications from the perspective of library and information access policies, as they should provide tools and resources to facilitate access to the new knowledge published in the fields of researchers, thus allowing them to be able to keep up high standards of referencing in their scientific work and publications. Although electronic tools have notably improved accessibility to scientific knowledge in the modern world, the claim for the establishment of adequate information access services (Ramesh Babu & Singh, ) is still valid to allow researchers to be aware of the most important ongoing literature in their fields.…”
Section: Discussionmentioning
confidence: 99%
“…Waldinger also showed that the amount of citations the scientific work of a doctoral student received through their entire subsequent scientific career was influenced by the status of their supervisor. Other factors, such as, the reputation of a department [ 9 ], the reputation the group leader [ 10 ], and access to resources and equipment [ 11 ], the number of full-professors on staff [ 12 ] influenced the research output of the academics involved in that group. Less information is available on the impact of student academic ability or prior research training on PhD outcomes: one analysis found that the reputation of a given department was more important for employment outcomes post-PhD than the accomplishments of the student during their studies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%